(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The stay in Mexico by Julian Nogueira, high official of the League of Na- tions, was the first formal and lasting contact between this international organization and the absent revolutionary country. During his stay, he would inquire into the Mexican political means to estimate the validity of the arguments justifying the distance from Geneva. He also carried out extensive propaganda work among key figures of the revolution, media and internationalists who years later would have an outstanding perfor- mance in the history of Mexico in the League of Nations, with the premise that the lack of understanding about the mission and activities of the or- ganization from Geneva was the basis of the Mexican rejection.